Sistema de levitação magnética como produto - Ferreira, Hugo Pelle (2019)
It is very often in undergraduate and graduate thesis, the development of prototypes for experiment purposes by students. Commonly, these prototypes are discontinued after their works are published because they are the only people able to operate it. In many occasions, a project's improvement can bring better results and become a commercial solution, providing innovation to the market and adding value to society. The aim of this thesis is the conversion of an undergraduate project about magnetic levitation, developed in UFRJ, on a low-cost product placed at the consumer electronics’ goods market in the decoration and didactic sectors and contribute to the Brazilian technology progress. In this system, an electromagnet produces an attraction force on a globe and suspends him. Its mechatronics nature provides the integration of multidisciplinary knowledges', as Electromagnetism, Control Systems, Power Electronics, Sensing and Instrumentation, Microcontrollers' programming, Computational Simulation, Microelectronics, Mechanics and Product Design. In this work, the levitation system hardware was improved to become compact and suitable to aesthetic requirements consistent to a product development. Beside its technical characteristics, new designs were introduced making it more attractive and including functionality and practicality. The market analysis using the users' behavior, like Design Thinking, and the opportunities and threats, revealed a great potential for technological products based on magnetic levitation, as proposed, destined to technology enthusiasts, and to decoration, lighting, entertainment and didactic sectors.